Racial disparities in acute care utilization among individuals with myasthenia gravis - Qi, Cynthia; Narayanaswami, Pushpa; Anderson, Ashley E. L.; Gelinas, Deborah; Li, Yuebing; Guptill, Jeffrey T.; Amirthaganesan, Dakshinamoorthy; Ward, Charlotte; Panchal, Rupesh; Goyal, Amit; Phillips, Glenn (Frontiers in Public Health, 2025)
ObjectiveIn myasthenia gravis (MG), evidence on the impact of social determinants of health on disparities in disease burden and healthcare resource utilization is limited. This study aimed to investigate the independent association between race/ethnicity and acute care utilization during the 2 years post-diagnosis among patients with MG.MethodsA retrospective cohort study was conducted among adults (≥18 years) with newly diagnosed MG in the United States using Optum’s de-identified Market Clarity Data from January 1, 2010, to December 31, 2019. Multivariable regression models were used to assess the association between acute care utilization and race/ethnicity, insurance, exacerbation at index, and other covariates.ResultsA total of 7,058 patients met the study inclusion criteria, of whom 57% (n = 4,052) identified as Caucasian, 6% (n = 445) African American, 3% (n = 235) Hispanic, 1% (n = 94) Asian, and 32% (n = 2,232) with missing race/ethnicity information. Compared with patients identifying as Caucasian, those identifying as African American had 37% higher odds of having an emergency department visit in year 1, and those identifying as Hispanic had 70% increase in odds of having a hospitalization event in year 2 post-diagnosis. Among other covariates, Medicaid usage, exacerbation at index, and number of outpatient visits were significantly associated with acute care utilization.ConclusionRacial disparities significantly impacted acute care utilization in the first 2 years post-MG diagnosis. Future studies should aim to examine specific factors that may contribute to disparities such as barriers to healthcare access, greater severity of MG symptoms, and poorly controlled disease.